Planning Today for Tomorrow’s Research: Analysis of Factors Influencing Participation in a Pediatric Cancer Research Biorepository - Labib, Rania M.; Hassanain, Omneya; Alaa, Maram; Ahmed, Safaa; Abou El-Naga, Sherif (Frontiers in Oncology, 2018)
Background: Biobanks have become a powerful tool that fosters biomedical research. The success of biobanks depends upon people’s perception and willingness to donate their samples for research. This is the first biorepository in Egypt, hence, little is known about the beliefs and attitudes of parents towards participation. Aim: To investigate the level of willingness of Egyptians to donate samples of themselves and of their children for research and the different factors influencing participation. Materials and Methods: A Structured questionnaire was designed covering multiple items expected to affect the enrollment decision. This was conducted in-person and data collected included demographic data, socioeconomic and educational level. Additionally, in the case of refusal, participants were asked about reasons behind their decision. Results: Only about 3.1% of patients have not been enrolled in the project and 0.3% has withdrawn. Three demographic factors were found having disparate trends in the decision-making process to participate or not: father’s education (p-value = 0.0001), mother’s education (p-value= 0.0001) and father’s age (p-value = 0.034). Conclusion: Egyptian parents were willing to participate their samples as well as their children samples in our research biorepository. The idea of participation was presented in an interview for consent form in a comprehensive transparent way giving participants the rights to refuse or withdraw at any time. Still, different communication approaches are needed with older highly educated parents to encourage them for participation.